Discovery of an Inhibitor for Bacterial 3-Mercaptopyruvate Sulfurtransferase that Synergistically Controls Bacterial Survival. Issue 12 (17th December 2020) - Croppi, Giorgia; Zhou, Yueyang; Yang, Rong; Bian, Yunfei; Zhao, Mingtao; Hu, Youtian; Ruan, Benfang Helen; Yu, Jing; Wu, Fang
Summary: H2 S-producing enzymes in bacteria have been shown to be closely engaged in the process of microbial survival and antibiotic resistance. However, no inhibitors have been discovered for these enzymes, e.g., 3-mercaptopyruvate sulfurtransferase (MST). In the present study, we identified several classes of inhibitors for Escherichia coli MST (eMST) through high-throughput screening of ∼26, 000 compounds. The thiazolidinedione-type inhibitors were found to selectively bind to Arg178 and Ser239 residues of eMST but hardly affected human MST. Moreover, the pioglitazone of this class concentration dependently accumulates the 3-mercaptopyruvate substrate and suppresses the H2 S and reactive sulfane sulfur products in bacteria. Importantly, pioglitazone could potentiate the level of reactive oxygen species in cellulo and consequently enhance the antimicrobial effects of gentamicin and macrophages in culture. This study has identified the bioactive inhibitor of eMST, paving the way for the pharmacological targeting of eMST to synergistically control the survival of E. coli . Graphical Abstract: Highlights: Identification of inhibitors for eMST by HTS screening of ∼26, 000 compounds On-target inhibition of eMST by thiazolidinedione-type inhibitors Identification and characterization of 3-MP and H2 S-reactive PAINS compounds Synergistic effects of eMST inhibitor for increasing ROS and killing of bacteria Abstract : H2 S generated by E. coli 3-mercaptopyruvate sulfurtransferase (eMST) maintains the ROS balance for bacterial survival. Croppi et al. identify a bioactive inhibitor for eMST that could suppress the production of H2 S and break ROS homeostasis in vitro and in living bacteria, leading to an improved killing effect for bacteria.